Spanish adaptation of the scale of attitudes towards palliative care: reliability and factor analysis - Leticia Ascencio Huertas (Psicooncologia, 2016)
This instrumental study presents the reliability and factor analysis as part of the Spanish adaptation of the Scale of Attitudes Palliative Care (PSST). I was done with the aim of knowing if the scale has psychometric properties, to be used to assess attitudes with health staff towards palliative care. He had a sample of 132 health professionals (80.3% women), aged between 20 and 40 years (M = 30, SD = 9.11). Exploratory and confirmatory analysis showed a satisfactory rate of reliability (Cronbach’s alpha: 0.807) to explain the 65,063% of the variance and factorial solution containing the correlations between the original variables and each of the factors. Among the most important factors we consider: Factor 1 refers to the process and guidelines for care units Palliative Care Factor 2 that relate personal experiences with death; and Factor 5 which relate to social support have Palliative Care. Concluding that the scale fulfills the psychometric properties for use in both clinical and research field.